2016
DOI: 10.1007/s11011-016-9805-2
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PPARα perpetuates sex differences in stroke reflected by peripheral immune mechanisms

Abstract: Peroxisome proliferator-activated receptor alpha (PPARα) is a nuclear receptor transcription factor that plays a role in immune regulation. Because of its expression in cerebral tissue and immune cells, PPARα has been examined as an important regulator in immune-based neurological diseases. Many studies have indicated that pre-treatment of animals with PPARα agonists induces protection against stroke. However, our previous reports indicate that protection is only in males, not females, and can be attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Although the function of PPARα in the brain remained elusive for a long time, more and more studies indicate that PPARα is involved in physiological and pathological brain functions (e.g., in the sleep-wake cycle [191,192], depression [193][194][195][196], epilepsy [197][198][199], stroke [200][201][202][203] and schizophrenia [204]). PPARα modulators (e.g., oleoylethanolamide, a natural PPARα ligand; Wy14643 and fibrates, two synthetic PPARα agonists) regulate dopamine and hippocampal brain-derived neurotrophic factor (BDNF) signaling pathways to rescue depression-related behaviors [193,195,196] and nicotinic acetylcholine receptors and endocannabinoid signaling to alleviate epilepsy and schizophrenia-like effects in mice [197,204].…”
Section: Pparα In Admentioning
confidence: 99%
“…Although the function of PPARα in the brain remained elusive for a long time, more and more studies indicate that PPARα is involved in physiological and pathological brain functions (e.g., in the sleep-wake cycle [191,192], depression [193][194][195][196], epilepsy [197][198][199], stroke [200][201][202][203] and schizophrenia [204]). PPARα modulators (e.g., oleoylethanolamide, a natural PPARα ligand; Wy14643 and fibrates, two synthetic PPARα agonists) regulate dopamine and hippocampal brain-derived neurotrophic factor (BDNF) signaling pathways to rescue depression-related behaviors [193,195,196] and nicotinic acetylcholine receptors and endocannabinoid signaling to alleviate epilepsy and schizophrenia-like effects in mice [197,204].…”
Section: Pparα In Admentioning
confidence: 99%
“…However, PPARα agonists did not have the same protective effect in female mice subjected to MCAO (Dotson et al, 2016b). The lack of therapeutic translation to females is likely due to lower expression of PPARα receptors in female tissues and immune cells and, therefore, a lack of immune regulation after stroke, specifically in the periphery (Jalouli et al, 2003; Dunn et al, 2007; Dotson et al, 2015, 2016b, 2016c). …”
Section: Translation Of Therapies To Both Sexesmentioning
confidence: 99%
“…# P 0.05, ## P 0.01, ### P 0.001 compared with the corresponding treatment in male MG. Reprinted from Metabolic Brain Disease, Role for microglia in sex differences after ischemic stroke: importance of M2, 30, 2015, 1515-1529, Bodhankar et al, V C Springer Science1Business Media New York 2015 not have the same protective effect in female mice subjected to MCAO (Dotson et al, 2016b). The lack of therapeutic translation to females is likely due to lower expression of PPARa receptors in female tissues and immune cells and, therefore, a lack of immune regulation after stroke, specifically in the periphery (Jalouli et al, 2003;Dunn et al, 2007;Dotson et al, 2015Dotson et al, , 2016bDotson et al, , 2016c.…”
Section: Translation Of Therapies Tomentioning
confidence: 99%
“…Previous studies have shown that, in cerebral I/R injury models, the infarction volumes and neurological deficits are more severe in PPARα knockout mice than those of the WT animals 26 . In this study, the infarct volumes, NADPH oxidase activity, and ROS content in the PPARα knockout mice of the saline control and Fasudil groups were 99.901 ± 4.792 and 100.823 ± 3.798 mm 3 , 98.000 ± 4.022 mm 3 and 101.390 ± 4.077 mm 3 , and 99.200 ± 4.240 and 102.590 ± 2.950 mm 3 , respectively; this concurred with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 92%